2019
DOI: 10.3390/cells8020183
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy as a Therapeutic Target to Enhance Aged Muscle Regeneration

Abstract: Skeletal muscle has remarkable regenerative capacity, relying on precise coordination between resident muscle stem cells (satellite cells) and the immune system. The age-related decline in skeletal muscle regenerative capacity contributes to the onset of sarcopenia, prolonged hospitalization, and loss of autonomy. Although several age-sensitive pathways have been identified, further investigation is needed to define targets of cellular dysfunction. Autophagy, a process of cellular catabolism, is emerging as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 161 publications
(205 reference statements)
1
47
0
1
Order By: Relevance
“…Since some studies have found that autophagy is activated, V-ATPase expression and lysosomal acidication are upregulated during tissue regeneration, 6,7,[80][81][82][83] and the observed phenomenon of lysosomal acidication in our work is consistent with the reported results. But our research provides…”
Section: Quantication Of Lysosomal Ph In Vitrosupporting
confidence: 93%
“…Since some studies have found that autophagy is activated, V-ATPase expression and lysosomal acidication are upregulated during tissue regeneration, 6,7,[80][81][82][83] and the observed phenomenon of lysosomal acidication in our work is consistent with the reported results. But our research provides…”
Section: Quantication Of Lysosomal Ph In Vitrosupporting
confidence: 93%
“…Skeletal muscle regenerative capacity declines with aging owing to a suppression of autophagy in multiple cell types (Lee et al, 2019). Hence, we envisioned that ARHGEF3 KO with autophagy-promoting effect would counteract the age-related decline in muscle regenerative capacity.…”
Section: Arhgef3 Ko Promotes Muscle Regeneration Through Autophagy Anmentioning
confidence: 99%
“…Increasing evidence shows that autophagy defective is implicated in aging and age-related pathologies. Thus, pharmacologically stimulated autophagy may ameliorate the symptoms of age-associated phenotypes [33,34]. Mitophagy is a specialized form of autophagy that degraded the damaged and dysfunctional mitochondria [35].…”
Section: Discussionmentioning
confidence: 99%